2016
DOI: 10.1016/j.cptl.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

The national consultation skills for pharmacy practice program in England

Abstract: Objective This paper aims to discuss the need to enhance pharmacy professionals' (pharmacists and pharmacy technicians) consultation skills in England and describe the development of a national consultation skills training programme to meet these needs. Methods The Centre for Pharmacy Postgraduate Education led on a project to create a consultation skills training programme for all pharmacy professionals across England. The programme embedded a set of consultation skills practice standards developed by a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“… 43 This holistic approach aligned with professional ambitions for pharmacists to adopt consultations based upon a shared care approach. 33 Despite resources being available to improve pharmacists’ consultation skills, 44 the challenge remains to what extent pharmacists are able to internalize and adopt a patient-centered approach within consultations (see “Domain 4: characteristics of stakeholders” section for further details).…”
Section: Mur Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 This holistic approach aligned with professional ambitions for pharmacists to adopt consultations based upon a shared care approach. 33 Despite resources being available to improve pharmacists’ consultation skills, 44 the challenge remains to what extent pharmacists are able to internalize and adopt a patient-centered approach within consultations (see “Domain 4: characteristics of stakeholders” section for further details).…”
Section: Mur Challengesmentioning
confidence: 99%
“… 42 It, therefore, remains to be seen to what extent pharmacists take the opportunity to uncover, identify, and address such complex health beliefs with the organizational constraints of MUR consultations. Despite initiatives to improve pharmacist consultation skills, 44 further improvements are needed as it has been found that many adherence intervention studies continue to fail to report tailoring the intervention to patient needs, adopting a shared care assessment or a concordant patient-centered approach. 79…”
Section: Mur Challengesmentioning
confidence: 99%
“…Effective communication is essential in ensuring positive health outcomes and best patient care. An increased emphasis has been put onto pharmacists' consultation skills, which are likely to become even more important with the advancement of a pharmacists' role in the coming years [4,30]. Research has found that after undergraduate education, medical graduates' communication abilities may deteriorate as a result of non-continuous training in this area [31].…”
Section: Discussionmentioning
confidence: 99%
“…CPs delivering MUR and NMS are required to be accredited in patient-centred consultation skills ( Jee et al, 2016 ). Distance learning has been available via the Centre for Pharmacy Postgraduate Education (CPPE) since 2014 ( CPPE, 2014 ).…”
Section: Introductionmentioning
confidence: 99%